Immunomodulation of experimental autoimmune encephalomyelitis by oral administration of copolymer 1 - Teitelbaum, Dvora (The National Academy of Sciences, 1999)
The activity of copolymer 1 (Cop 1, Copaxone, glatiramer acetate) in suppressing experimental autoimmune encephalomyelitis (EAE) and in the treatment of multiple sclerosis patients when injected parenterally has been extensively demonstrated. In the present study we addressed the question of whether Cop 1 can induce oral tolerance to EAE similar to myelin basic protein (MBP). We now have demonstrated that oral Cop 1 inhibited EAE induction in both rats and mice. Furthermore, oral Cop 1 was more effective than oral MBP in suppressing EAE in rats. The beneficial effect of oral Cop 1 was found to be associated with specific inhibition of the proliferative and Th1 cytokine secretion responses to MBP of spleen cells from Cop 1-fed mice and rats. In all of these assays, oral Cop 1 was more effective than oral MBP. The tolerance induced by Cop 1 could be adoptively transferred with spleen cells from Cop 1-fed animals. Furthermore, Cop 1-specific T cell lines, which inhibit EAE induction in vivo, could be isolated from the above spleen cells. These T cell lines secrete the anti-inflammatory cytokines IL-10 and transforming growth factor type β, but not IL-4, in response to both Cop 1 and MBP. In conclusion, oral Cop 1 has a beneficial effect on the development of EAE that is associated with down-regulation of T cell immune responses to MBP and is mediated by Th2/3 type regulatory cells. These results suggest that oral administration of Cop 1 may modulate multiple sclerosis as well.